30 pī Samnak Sinlapa læ Watthanatham, Mahāwitthayālai Rātchaphat Thēpsattrī (Samnak Sinlapa læ Watthanatham, Mahāwitthayālai Rātchaphat Thēpsattrī, 2009)
On tradition and culture of Lop Buri Province, Central Thailand; volume commemorating 30th anniversary of Samnak Sinlapa lae Watthanatham, Mahawitthayalai Ratchaphat Thepsattri.